INTERCULTURAL COMPETENCE DEVELOPMENTAL MODELS – THEORY AND PRACTICE THROUGH COMPARATIVE ANALYSIS - Vegh, Judit; Luu, Lan Anh Nguyen (PEOPLE: International Journal of Social Sciences, 2019)
Intercultural competence is currently an area of research in which new approaches and perspectives appear in large numbers every year. Given the importance of intercultural competence there is a need for a consensus within this multidisciplinary approach.This comparative analysis focuses on two developmental models of intercultural competence, the Reflective Intercultural Competence Assessment model, and the Developmental Model of Intercultural Sensitivity. The purpose of this paper is to discover guidelines and future direction for current and potential use of these developmental models. This study focuses on a general comparison line which can be applicable in further intercultural competence model studies.